计算,快(2a-b)(4a^2+b^2+2ab)-a(3a-b)(3a+b)
1个回答
(2a-b)(4a^2+b^2+2ab)-a(3a-b)(3a+b)
=(2a)³-b³-a(9a²-b²)
=8a³-b³-9a³+ab²
=-a³-b³+ab²
相关问题
计算分式:b^4/(a-b)^2 乘 a^3+ab^2-2a^2b/b^3 除以b^2-a^2/ab+b^2
计算:b/a-b加上b^3/a^3-2a^2b+ab^2除以ab+b^2/b^2-a^2
计算:7a²b-(-4a²b+5ab²)-2(2a²b-3ab²)
计算(a^3-4a^2b-a+4ab^2)/a(a-2b+1)
a^3+a^2b+ab^2-a^2b-ab^2-b^2 计算,
计算a+9b/3ab-a+3b/3ab=( ) a^2b^3/(2a^-1b^2)^-3=( )
计算 (a^2b-ab-a+1)/(ab^2+3ab-b-3)÷(a^2+a_2)/(b^2+b-6)
计算a²/(a²-2ab)×√(a²b-4ab²+4b^3)/a+b√(a/b)
计算(-a^2)3^b^3-2b*(a^3)^2*b^2-a^4*(-b^^3*(-a)^2
计算(-a^2)3^b^3-2b*(a^3)^2*b^2-a^4*(-b)^3*(-a)^2